2014
DOI: 10.1088/1054-660x/24/10/105111
|View full text |Cite
|
Sign up to set email alerts
|

Mode-locked Er-doped fiber laser based on liquid phase exfoliated Sb2Te3topological insulator

Abstract: In this paper, femtosecond pulse generation in an Er-doped fiber laser is reported. The laser is passively mode-locked by an antimony telluride (Sb 2 Te 3 ) topological insulator (TI) saturable absorber (SA) placed on a side-polished fiber. The Sb 2 Te 3 /chitosan suspension used to prepare the SA was obtained via liquid phase exfoliation from bulk Sb 2 Te 3 .Ultra-short 449 fs soliton pulses were generated due to the interaction between the evanescent field propagated in the fiber cladding and the Sb 2 Te 3 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(35 citation statements)
references
References 39 publications
0
35
0
Order By: Relevance
“…The Sb exfoliation to obtain antimonene is now in the spotlight because its sheets are expected to present low thermal conductance, semiconducting character and tunable bandgap from 0 to 2.28 eV, which is suitable for optoelectronic applications . Alternatively, 2D Sb 2 Te 3 , which belongs to metal transition trichalcogenides, is an attracting topological insulator with good thermoelectric performance . Some authors have demonstrated the promising potential of Sb 2 Te 3 nanosheets with topological insulator and thermoelectric performance for laser fabrication, thermoelectric and nanoelectronics applications …”
Section: Introductionmentioning
confidence: 99%
“…The Sb exfoliation to obtain antimonene is now in the spotlight because its sheets are expected to present low thermal conductance, semiconducting character and tunable bandgap from 0 to 2.28 eV, which is suitable for optoelectronic applications . Alternatively, 2D Sb 2 Te 3 , which belongs to metal transition trichalcogenides, is an attracting topological insulator with good thermoelectric performance . Some authors have demonstrated the promising potential of Sb 2 Te 3 nanosheets with topological insulator and thermoelectric performance for laser fabrication, thermoelectric and nanoelectronics applications …”
Section: Introductionmentioning
confidence: 99%
“…At the same time, they have been successfully utilized as SA for the realization of mode-locking [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. TISA could be fabricated by the mechanical exfoliation, the molecular beam epitaxy (MBE) growth, the vapor-liquidsolid growth, chemical exfoliation, the mechanical triturating and the filmy method in polyvinyl alcohol [25,[42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…This property originates from a join of timereversal symmetry and spin-orbit interactions [10]. Among them, three main TIs have been used as a SA: bismuth selenide (Bi 2 Se 3 ) [11,12], bismuth telluride (Bi 2 Te 3 ) [13][14][15][16], and antimony telluride (Sb 2 Te 3 ) [17][18][19][20]. For instance, Sb 2 Te 3 is characterized by a high nonlinear refractive index of 2.606 × 10 −9 m 2 ∕W [21].…”
mentioning
confidence: 99%
“…In comparison to graphene, the properties of TIs create a possibility to use a bulk material instead of monoor few-layer, which translates into a more straightforward technological process. Previous contributions were mainly focused on the operation in anomalous dispersion regime, where no dispersion compensation is required [11][12][13][14][15]17,18]. The first demonstration of a dissipative soliton generation with the use of TI was presented by Chi et al at 1.06 μm [16].…”
mentioning
confidence: 99%